The development of the unified Baltic Sea Chart Datum 2000 (BSCD2000) height transformation grid: an unprecedented example of height system unification based on state-of-the-art marine geoid modelling - Joachim Schwabe; Sander Varbla; Jonas Ågren; Hergeir Teitsson; Artu Ellmann; Gunter Liebsch; René Forsberg; Gabriel Strykowski; Mirjam Bilker-Koivula; Ivars Liepiņš; Eimuntas Paršeliūnas; Kristian Keller; et al. (Journal of Geodesy, 2026)
The shallow Baltic Sea is a vital waterway with dense shipping traffic, requiring accurate and reliable nautical charts for safe navigation. Until recently, different realisations of the mean sea level were used in the paper charts of each country, sometimes even between harbours. This created obstacles for the digitalisation of ship navigation, including electronic nautical charts combined with satellite-based positioning. To resolve this, the Baltic Sea Hydrographic Commission decided in 2013 to introduce the Baltic Sea Chart Datum 2000 (BSCD2000) as a common height/depth reference system for the maritime sector in the Baltic Sea. The new reference level for all depth and water level information is strictly the quasigeoid, which is practically identical to the geoid at sea. The BSCD2000 is defined in accordance with the European reference systems: the European Terrestrial Reference System 1989 (ETRS89) for ellipsoidal coordinates and the European Vertical Reference System (EVRS) for physical heights. This enables the practical implementation of the zero level through a seamless height transformation grid with standard uncertainties of approximately 1–2 cm, which is harmonised with national coordinates, heights, and height reference surfaces. To the authors’ knowledge, this level of harmonisation is unprecedented in the maritime sector and exemplifies the value of the unification of height systems in geodesy. The paper outlines the foundations of the BSCD2000 and the approach to construct the BSCD2000 height transformation grid. While the computation of the gravimetric marine quasigeoid model is based on well-established methods, special focus is placed on practical harmonisation across national borders and along the coastline. To this end, a novel fitting and blending scheme based on distance maps was developed. Finally, comparison of the new gravimetric marine quasigeoid solution with a preliminary geometric marine geoid model based on SWOT altimetry data and hydrodynamic modelling confirmed good agreement within a few centimetres in most areas of the Baltic Sea.

Delayed plant genetic responses to forest edge dynamics and their conservation implications - Lore Hostens; Christophe Metsu; Elissar Alam; Kasper Van Acker; Gerrit Peeters; Sander de Beer; Yannick Gansemans; Eugenija Kupcinskiene; Lina Jociene; Edvina Krokaite‐Kudakiene; Jolina Paulssen; Leonie Mazalla; et al. (Conservation Biology, 2026)
Understanding genetic responses to forest dynamics is essential for predicting the long‐term viability of understory plant populations and for developing effective conservation strategies. We investigated genetic extinction debt and colonization credit in broad‐leaved enchanter's nightshade ( Circaea lutetiana ), a clonal forest understory species, across its European range. Using pooled genotype‐by‐sequencing data from 40 forest edge and core populations, we examined to what extent population size, latitude, and historical changes in forest configuration may predict genetic diversity. Historical forest configuration profoundly shaped present‐day genetic diversity. Long‐established forest edge populations exhibited significantly reduced allelic richness (−9%) compared with core populations, indicating the partial payoff of a genetic extinction debt. In contrast, populations from recently established forest edges maintained allelic richness similar to core populations, suggesting delayed population genetic responses to land‐use changes. Finally, populations established in areas that were afforested during the past 250 years exhibited lower allelic richness (−10%) than historical forest core populations, indicating a delay in genetic recovery and thus a potential genetic colonization credit. Our results highlight that C. lutetiana populations are not at equilibrium with the current forest configuration, underscoring the role of lagged genetic responses across very long periods. Population size, and to a lesser extent connectivity, further mediated genetic diversity, with smaller, isolated populations being particularly vulnerable to genetic erosion. Given the limited research on delayed evolution in forest understory species, our results improve understanding of extinction risk dynamics and underscore the need for history‐informed restoration efforts.

Stable carbon isotope fractionation during microbial turnover of sucrose in different media: Soils, carbon-free quartz and liquid media - Klara Cecilia Gunnarsen; Jakob Magid; Per Ambus; Bent T. Christensen; Sander Bruun; Saadatullah Malghani (Applied Soil Ecology, 2025)

Prematuration differences in male and female Atlantic cod: Investigating sex ratio, length and ecotype disparities in juveniles - Sander Vollmerhaus Digre; Per Erik Jorde; Arild Folkvord; Jakob Hemmer‐Hansen; Halvor Knutsen (Journal of Fish Biology, 2025)
Sexual size dimorphism (SSD) and skewed sex ratios are common in the animal kingdom, and marine fishes, such as the Atlantic cod ( Gadus morhua ), are no exception. This study utilized newly discovered sex‐linked genetic markers to investigate young‐of‐the‐year cod in the Skagerrak system, comprising approximately 2700 individuals from North Sea and fjord ecotypes. Overall, no significant difference in sex ratio was observed overall (51% females, 49% males), with consistent findings across 14 locations and three sheltering degrees. Although slightly more females were found in exposed areas, and slightly more males in sheltered regions, these differences were not significant. Size variation between female and male cod was generally negligible. These results indicate a likely purely genetic sex determination system in Atlantic cod and a lack of prematuration growth differences between sexes. This research enhances our understanding of the Atlantic cod, providing more insight into the Atlantic cod population in the Skagerrak and emphasizing the importance of genetic factors in sex determination.

Spatial and seasonal variability in benthic impact of mussel farms: Predicting and mitigating impacts using ambient oxygen conditions - Per Bergström; Matthew Hargrave; Jesper Hassellöv; Christophe Sanders; Mats Lindegarth (Science of The Total Environment, 2024)

Sampling bias misrepresents the biogeographical significance of constitutive mixotrophs across global oceans - Suzana Gonçalves Leles; Aditee Mitra; Kevin John Flynn; Urban Tillmann; Diane Stoecker; Hae Jin Jeong; JoAnn Burkholder; Per Juel Hansen; David A. Caron; Patricia M. Glibert; Gustaaf Hallegraeff; John A. Raven; et al. (Global Ecology and Biogeography, 2019)
Aim Most protist plankton are mixotrophic, with potential to engage in photoautotrophy and phagotrophy; however, the ecology of these organisms has been misdiagnosed for over a century. A large proportion of these organisms are constitutive mixotrophs (CMs), with an innate ability to photosynthesize. Here, for the first time, an analysis is presented of the biogeography of CMs across the oceans. Location Global marine ecosystems. Time period 1970–2018. Major taxa studied Marine planktonic protists. Methods Records for CM species, primarily from the Ocean Biogeographic Information System (OBIS), were grouped by taxonomy and size to evaluate sampling efforts across Longhurst's oceanic provinces. Biases were evaluated through nonparametric tests and multivariate analysis. Biogeographies of CMs from OBIS data were compared with data from studies that specifically targeted these organisms. Results Constitutive mixotrophs of different taxonomic groups, across all size ranges, are ubiquitous. However, strong database biases were detected with respect to organism size, taxonomic groups and region. A strong bias was seen towards dinophytes. Species Main conclusions Constitutive mixotrophs are dominant members of organisms traditionally termed “phytoplankton”. However, lack of routine protocols for measuring phagotrophy in “phytoplankton” protists has led to widespread misrepresentation of the fundamental nature of marine planktonic primary producers; most express both “animal‐like” and “plant‐like” nutrition. Our results have implications for studies of the global biogeography of plankton, of food web dynamics (including models) and of biogeochemical cycling in the oceans.

A finite element model to assess transtibial prosthetic sockets with elastomeric liners - John C. Cagle; Per G. Reinhall; Kate J. Allyn; Jake McLean; Paul Hinrichs; Brian J. Hafner; Joan E. Sanders (Medical & Biological Engineering & Computing, 2018)

Tipping Toward Sustainability: Emerging Pathways of Transformation - Frances Westley; Per Olsson; Carl Folke; Thomas Homer-Dixon; Harrie Vredenburg; Derk Loorbach; John Thompson; Måns Nilsson; Eric Lambin; Jan Sendzimir; Banny Banerjee; Victor Galaz; et al. (Ambio, 2011)

Porous Magnesium Aluminometasilicate Tablets as Carrier of a Cyclosporine Self-Emulsifying Formulation - Camilla Sander; Per Holm (AAPS PharmSciTech, 2009)

Remote sensing and GIS in hydrogeology - Jörn Hoffmann; Per Sander (Hydrogeology Journal, 2007)

Lineaments in groundwater exploration: a review of applications and limitations - Per Sander (Hydrogeology Journal, 2007)

Comparing Deterministic and Probabilistic Risk Assessments. A case study at a closed steel mill in southern Sweden (7 pp) - Per Sander; Tomas Öberg (Journal of Soils and Sediments, 2006)

Water-Well Siting in Hard-Rock Areas: Identifying Promising Targets Using a Probabilistic Approach - Per Sander (Hydrogeology Journal, 1997)